2013
DOI: 10.1021/jf400787j
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of Flaxseed Oil Using a Benchtop Spray Dryer for Legume Protein–Maltodextrin Microcapsule Preparation

Abstract: Flaxseed oil was microencapsulated employing a wall material matrix of either chickpea (CPI) or lentil protein isolate (LPI) and maltodextrin using a benchtop spray dryer. Effects of emulsion formulation (oil, protein and maltodextrin levels) and protein source (CPI vs LPI) on the physicochemical characteristics, oxidative stability, and release properties of the resulting capsules were investigated. Microcapsule formulations containing higher oil levels (20% oil, 20% protein, 60% maltodextrin) were found to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
44
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(60 citation statements)
references
References 35 publications
9
44
0
2
Order By: Relevance
“…To meet consumers’ demand for clean labels and natural foods, the microencapsulation of food‐grade of oils and the addition of natural antioxidants are common strategies for protecting unsaturated fatty acids from lipid oxidation. The microencapsulation of the omega‐3 oils by spray drying has been used to improve the oxidative stability of oils, but the complex coacervation process and insufficient protection of the oil remain major obstacles that must be addressed . Natural antioxidants are convenient for wide use as additives.…”
Section: Introductionmentioning
confidence: 99%
“…To meet consumers’ demand for clean labels and natural foods, the microencapsulation of food‐grade of oils and the addition of natural antioxidants are common strategies for protecting unsaturated fatty acids from lipid oxidation. The microencapsulation of the omega‐3 oils by spray drying has been used to improve the oxidative stability of oils, but the complex coacervation process and insufficient protection of the oil remain major obstacles that must be addressed . Natural antioxidants are convenient for wide use as additives.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to the materials used in the production of microcapsules, polysaccharides, such as alginate, starch and cellulose; and proteins as collagen and gelatin are widely used due to their ability to bind to flavour compounds, plus their biodegradability and low cost. They are used for the production of those materials in the food and pharmaceutical area (Can Karaca et al, 2013;Soliman, 2013). Researchers have been recently exploring the use of chitosan as an encapsulating agent (Peng et al, 2010a;2010b;Estevinho et al, 2013a;Nuisin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Continuous phase of O/W emulsions generally include a polysaccharide, such as MD, when the emulsion is intended to be spray dried to produce microcapsules, where MD acts as a coat material (Karaca, Low, & Nickerson ; Karaca, Nickerson, & Low, ; Ramakrishnan et al., ; Taneja, Ye, & Singh, ; Turasan, Sahin, & Sumnu, ). However, MD can also be used to prepare stable emulsions as the final product by using significantly less homogenization power, similar to the present study as well as the previous ones (Dokic‐Baucal, Dokic, & Jakovljevic, ; Julio et al., ; Klinkesorn et al., ; Udomrati et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…Evaluation of each response individually by three‐way ANOVA analysis revealed that all variables (emulsifier and oil concentrations, type of the emulsifier) and their interactions had significant effects ( P < 0.05) on the droplet size of the emulsions (Table ). In all emulsions prepared with MD in the continuous phase, droplet size significantly increased with increasing oil concentration, due to the insufficient amount of emulsifiers to adsorb at the O/W interface, leading to coalescence and larger oil droplets (Karaca, Low, et al., ; Karaca, Nickerson et al, ; Taneja et al., ; Turasan et al., ). Likewise, all emulsions had the same trend of decreasing droplet size with increasing emulsifier concentration, due to the efficient binding of the emulsifiers at the interface, and thereby, reducing the droplet size (Nielsen et al., ; Taneja et al., ).…”
Section: Resultsmentioning
confidence: 99%